Standards, Practical Tools in Dealing with Climate Change - Dulbert T, Biatna (Eksergi, 2010)
Drastic climate change is becoming an increasingly serious threat to the survival of living beings on this planet. Various effects have been caused by climate change such as rising temperatures, floods, rising sea level, the uncertain season and other radical changes. Other than forest destruction, as well as industry and transportation use fossil fuels contributed in exacerbating climate change. Indonesia, have adopted identical to the four Green House Gases (GHG) into the SNI via reprints. As a developing country and the condition of Indonesias forests and peatland in the tropics, it is more easy going deforestation and degradation. Indonesia is concentrated to develop standards in deforestation field based decreased functions of tropical rain forests as carbon sinks are big enough, not to mention the peatland carbon stocks that have high potential around 36 Gton CO2 from 22 million hectares only. The development of ISO standards in measurements and calculations the Greenhouse Effect, Product Recycling, Promoting Environmental good, Energy Efficiency, Consumer Aware Environmental, very useful and contribute to tackle climate change significantly with the implementation of international standards. The most important thing now is how far the destruction of nature caused by human habits that are not environmentally friendly. Increasing understanding about the scale of change needed to tackle global warming, government, business and civil society should be able to perform the necessary steps and face the need to work in partnership to address such a change. In the long term the benefits of addressing climate change will far outweigh the impact costs . But in the short term, governments, business, and civil society will be more willing to bear those costs if they know their counterparts and competitors use standards, as a practical tool in dealing with climate change.